Intelligence and Creativity in problem solving: The importance of test features in cognition research - Jaarsveld, Saskia; Lachmann, Thomas (Frontiers in Psychology, 2017)
This paper discusses the importance of three features of psychometric test for cognition research: construct definition, problem space, and knowledge domain. Definition of constructs, e.g., intelligence or creativity, forms the theoretical basis for test construction. Problem space, being well or ill-defined, is determined by the cognitive abilities considered to belong to the constructs, e.g., convergent thinking to intelligence, divergent thinking to creativity. Knowledge domain and the possibilities it offers cognition are reflected in test results. We argue that a) comparing results of tests with different problem spaces is more informative when cognition operates in both tests on an identical knowledge domain, and b) intertwining of abilities related to both constructs can only be expected in tests developed to instigate such a process. Test features should guarantee that abilities can contribute to self-generated and goal-directed processes bringing forth solutions that are both new and applicable. We propose and discuss a test example that was developed to address these issues.